2003
DOI: 10.3349/ymj.2003.44.5.816
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear Cytoplasmic Pseudoinclusions in Pituitary Adenomas

Abstract: Intranuclear pseudoinclusions are well known in papillary carcinomas of the thyroid gland, hepatocellular carcinomas, meningiomas, paragangliomas, pheochromocytomas, and melanomas. Only two papers on the intranuclear inclusions of adenohypophyseal cells in humans have been reported. This study found that intranuclear cytoplasmic pseudoinclusions occur frequently in pituitary adenoma cases (70.3%, 97 of 138 pituitary adenomas) and are uncommon in normal pituitary tissue (11.1%, 1 of 9 normal pituitary tissues).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These inclusions are associated with various clinical conditions including cancer, obesity, diabetes, nonalcoholic fatty liver disease, Wilson disease, and amiodarone toxicity and observed in many tissue types including liver [1], [2], [3], [4]. The origins of these inclusions are unknown, however their presence has been used in histo-pathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These inclusions are associated with various clinical conditions including cancer, obesity, diabetes, nonalcoholic fatty liver disease, Wilson disease, and amiodarone toxicity and observed in many tissue types including liver [1], [2], [3], [4]. The origins of these inclusions are unknown, however their presence has been used in histo-pathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to remember that biotin inclusions, described in several tumors, cause false‐positive immunostaining reactions in avidin–biotin‐based detection protocols . Pseudoinclusions are classically found in papillary thyroid carcinoma and meningioma, but can occur in a number of other malignant and benign lesions, including usual ductal hyperplasia of the breast or pituitary adenoma . Appreciation of NPIs during evaluation of brain tumors strongly supports a diagnosis of meningioma over other entities .…”
mentioning
confidence: 98%
“…These intranuclear inclusions are found in not only pituitary tumors [20] but also other tumors including meningioma [21], paraganglioma [4], phenochromocytoma [4] and thyroid carcinoma [8] in humans. Intranuclear inclusions in pituitary tumors are formed by cytoplasmic invagination and composed of cytoplasmic organelles, such as rough endoplasmic reticulum, the Golgi apparatus and the secretory granules [20]. In addition, it was reported that there are no significant differences in the frequency of the intranuclear inclusions between the functional and non-functional pituitary tumors [20].…”
mentioning
confidence: 99%
“…Intranuclear inclusions in pituitary tumors are formed by cytoplasmic invagination and composed of cytoplasmic organelles, such as rough endoplasmic reticulum, the Golgi apparatus and the secretory granules [20]. In addition, it was reported that there are no significant differences in the frequency of the intranuclear inclusions between the functional and non-functional pituitary tumors [20]. To our best knowledge, there is no report about intranuclear inclusions in pituitary tumors in cats.…”
mentioning
confidence: 99%